THE DISTINCTION BETWEEN NUSYŪZ AND DOMESTIC VIOLENCE: The Relevance of Muhammad Sa’id Ramadhan Al-Buthi Thought in Contemporary Context - Hakim, Abdul; Alkosibati, Ali (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Domestic violence is often justified as being legitimized in fiqh. It culminates in a discussion about nusyūz when a husband can beat his wife in response to her resistance. Al-Buthi is a scholar who discusses nusyūz and domestic violence with great vigor. In the context of defending the compatibility of Islamic law in the contemporary era, he argues that nusyūz and domestic violence are not the same. This paper explains Al-Buthi's thoughts on the distinction between nusyūz and domestic violence. Data were gathered by investigating the works of Al-Buthi and other scholars' works related to his thought on the discussed topic and then analyzed qualitatively. This study argues that Al-Buthi emphasizes that nusyūz in Islam is different from domestic violence. In the case of nusyūz, even though the husband is allowed to beat his wife, it is not permissible to beat her seriously. If there are defects caused, then the husband must be responsible. By just refining the meaning of beating, Al-Buthi provides an understanding that the nusyūz rules in Islamic law are still relevant to the current context, particularly to women's rights. Apart from his argument on the stance on women's rights, his thoughts tend to the side of Islamic legal conservatism.[Kekerasan dalam rumah tangga seringkali dijustifikasi sebagai praktek yang dilegitimasi dalam fikih. Puncaknya dalam diskusi tentang nusyūz, ketika seorang suami dapat memukul istrinya sebagai respon atas pembangkangannya. Al-Buthi adalah seorang ulama yang cukup intens membahas nusyūz dan kekerasan dalam rumah tangga. Dalam konteks mempertahankan kompatibilitas hukum Islam di era kontemporer, ia berpendapat bahwa nusyūz dan KDRT tidaklah sama. Tulisan ini menjelaskan pemikiran Al-Buthi tentang distingsi antara nusyūz dan kekerasan dalam rumah tangga. Data dikumpulkan dengan menelaah karya-karya Al-Buthi dan artikel jurnal yang terkait dengan pemikirannya dan kemudian dianalisis secara kualitatif. Penelitian ini menemukan bahwa Al-Buthi hanya menegaskan nusyūz dalam Islam berbeda dengan kekerasan dalam rumah tangga. Dalam kasus nusyūz, meskipun suami diperbolehkan memukul istrinya, tidak boleh memukulnya dengan serius. Jika ada cacat yang ditimbulkan, maka suamilah yang harus bertanggung jawab. Dengan hanya memperhalus makna dan konsekuensi memukul, Al-Buthi berargumentasi bahwa aturan nusyūz dalam hukum Islam masih relevan dengan konteks saat ini, khususnya menyangkut hak-hak perempuan. Terlepas dari argumennya membela hak perempuan, pemikirannya cukup lebih lebih menonjolkan konservatisme hukum Islam.]